Assessment of antimicrobial use among patients admitted to a tertiary care hospital: A prospective observational study using World Health Organization AWaRe and Indian Council of Medical Research guidelines - Ankur; Prem Kapur; Neetu Shree; Rajiv Chhabra; Kiran Dubey (Indian Journal of Pharmacology, 2026)
Abstract: BACKGROUND: Antimicrobial resistance has emerged as a global challenge to human health, primarily due to inappropriate use. The ICMR reports revealed that there is sustained rise of AMR in India. OBJECTIVE: The objective of this study was to evaluate the prescribing pattern of antimicrobials and rationality of empiric antimicrobial use in a tertiary care hospital. METHOD: A prospective observational study, approved by the Institutional Ethical Committee (IEC) was conducted for a period of one year from July 2023 to June 2024 among the admitted patients of the hospital. The prescribing pattern was assessed in accordance with AWaRe classification and prescribing indicators by the World Health Organization. Rational use of empiric therapy was assessed as per the ICMR 2022 guidelines. RESULTS: A total of 653 antimicrobials were prescribed to 289 patients and maximum antimicrobials were from Watch category (55.7%), followed by Access (40.4%), and Reserve category (2.3%). The respiratory tract infection was the most common indication to start empiric antimicrobial therapy. The empiric therapy was appropriate for 80.3% patients as per the ICMR guidelines. The observed deviations were the empiric use of amikacin for bone & joint infection, duplicate beta lactam therapy, 3rd generation cephalosporins for uncomplicated urinary tract infection, the use of Reserve antibiotic-linezolid, and the use of piperacillin/tazobactam for sepsis patients. CONCLUSION: There is a need to strengthen the antimicrobial stewardship program by adhering to the national guidelines in the hospital settings, to prevent antimicrobial misuse and resistance. The use of Assess category should be encouraged, Watch category should be used under proper monitoring and the use of Reserve antimicrobials as an empiric therapy should be avoided.